2017
DOI: 10.18352/jsi.527
|View full text |Cite
|
Sign up to set email alerts
|

How the participation style in local youth councils contributes to the civic engagement of young people

Abstract: A B S T R A C T How the participation style in local youth councils contributes to the civic engagement of young peopleLocal youth councils are increasingly seen as suitable places for young people to come together and act on issues of public concern. However, little is known about the style of young people's participation in councils and whether they do indeed focus on young people during their discussions and activities. To discover this, a multiple case study (n=6) was used to identify the style in which yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We identified specific aspects of mission, membership, structure, and activities to provide markers as to which model is implicit in the council operation. Feringa and Tonkens' (2017) use of bonding and bridging to reflect participation in youth councils may also be of use here. Participation that focuses mostly on bonding is consonant with youth development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified specific aspects of mission, membership, structure, and activities to provide markers as to which model is implicit in the council operation. Feringa and Tonkens' (2017) use of bonding and bridging to reflect participation in youth councils may also be of use here. Participation that focuses mostly on bonding is consonant with youth development.…”
Section: Discussionmentioning
confidence: 99%
“…A recently reported multiple case study (Feringa & Tonkens, 2017) conducted in the Netherlands specifically focused on various participation styles in local youth councils. One of the study findings was that participation was predominantly "internally focused" rather than deliberation about civic issues or issues affecting other young people.…”
Section: Background and Purposementioning
confidence: 99%
“…In the Netherlands, there are many opportunities for youth to participate in public affairs, in particular youth councils appointed by municipalities and/or by secondary schools. However, research shows that there are sharp differences within the youth population: adolescents from higher socio-economic background are more represented than adolescents from the lower socioeconomic background in youth councils (Feringa, 2013;Feringa & Tonkens, 2017). This strongly correlates with differences in parents' educational levels (high/low) and tier of secondary education of adolescents (pre-university/vocational and pre-vocational).…”
Section: Alliance Introduction and Recruitment Strategymentioning
confidence: 99%
“…Research on children's participation arenas is vast nowadays (Feringa and Tonkens 2017;Sant and Davies 2018;Taft and Gordon 2013), and though earlier research has indicated the benefits of children's participation in general (Sinclair 2004), critical voices appear alongside. Some (Hart 1992;Lundy 2018) suggest that children's participation often appears as non-participation and consultation, and adults mostly dominate the agendas and the means of participation.…”
Section: Introductionmentioning
confidence: 99%